Core competencies for academic reference librarians in Croatia - Hebrang Grgić, Ivana; Živković, Daniela (2012)
The paper presents results of a survey of reference librarians in Croatian academic libraries. The survey is a part of an international study. Survey findings provide valuable data regarding skills and competencies needed in the reference departments today and in the future. Three groups of skills and competencies are analysed – general skills, technology skills and personal skills. Conclusions are made about the present competencies of Croatian reference librarians in academic libraries as well as about the importance of lifelong learning for improving their competencies in future.
ENG